Identification of DNA Methylation Changes That Predict Onset of Post-traumatic Stress Disorder and Depression Following Physical Trauma - Martin, Carina A.; Vorn, Rany; Schrieber, Martin; Lai, Chen; Yun, Sijung; Kim, Hyung-Suk; Gill, Jessica (Frontiers in Neuroscience, 2021)
Post-traumatic stress disorder (PTSD) and major depressive disorder (MDD) are commonly experienced after exposure to highly stressful events, including physical trauma, yet, biological predictors remain elusive. Methylation of DNA may provide key insights, as it likely is reflective of factors that may increase the risk in trauma patients, as DNA methylation is altered by previous stressors. Here, we compared DNA methylation patterns using bisulfite sequencing in patients with a physical trauma that required more than a 24-hour hospitalization (n = 33). We then compared DNA methylation in patients who developed and compared the following groups (1) PTSD and MDD; n = 12), (2) MDD (patients with MDD only; n = 12), and (3) control (patients who did not have PTSD or MDD; n = 9), determined by the PTSD Checklist (PCL-5) and Quick Inventory of Depressive Symptomatology (QIDS) at 3-months follow-up. We identified 17 genes with hypermethylated cytosine sites and 2 genes with hypomethylated sites in comparison between PTSD and control group. In comparison between MDD and control group, we identified 12 genes with hypermethylated cytosine sites and 6 genes with hypomethylated sites. Demethylation of these genes altered the CREB signaling pathway in neurons, and may represent a promising therapeutic development target for PTSD and MDD. Our findings suggest that epigenetic changes in these gene regions potentially relate to the onset and symptomology of PTSD and MDD and could be used as potential biomarkers in predicting the onset of PTSD or MDD following traumatic events.